Tympanogram and Audiogram Presentation after Tympanomastoidectomy Surgery Using Musculus Temporalis Fascia Profunda Graft and Composite Graft (Medico Legal Update, 2020)
In recent decades, there has been an increase in the use of composite graft in the closure of the tympanicmembrane perforation. The aim of this research is to know the change of tympanogram and audiogrampresentation after tympanomastoidectomy surgery using musculus temporalis fascia profunda graft andcomposite graft. Experimental research was being conducted on 22 Otitis Media Suppurative Chronicpatients without cholesteatoma such as 14 patients using musculus temporalis fascia profunda graft and8 patients using composite graft. The Audiometric tests were being administered twice, before and aftertympanomastoidectomy surgery, in other hand tympanometry test was being performed after surgery. Dataanalysis using independent-t test, paire-t test, and chi square test. The research has shown that the Pure ToneAudiometry post-surgeries were being found higher on composite graft (68,4) in comparison with musculustemporalis fascia profunda graft (55,1), but statistically non-significant (p>0,05). On the contrary, on fasciagraft group was being found significantly higher 1,47 than amplitudo composite graft (0,87), statisticallysignificant (p